2021
DOI: 10.3389/fonc.2021.710909
|View full text |Cite
|
Sign up to set email alerts
|

Development and Validation of a 18F-FDG PET-Based Radiomic Model for Evaluating Hypermetabolic Mediastinal–Hilar Lymph Nodes in Non-Small-Cell Lung Cancer

Abstract: BackgroundAccurate evaluation of lymph node (LN) status is critical for determining the treatment options in patients with non-small cell lung cancer (NSCLC). This study aimed to develop and validate a 18F-FDG PET-based radiomic model for the identification of metastatic LNs from the hypermetabolic mediastinal–hilar LNs in NSCLC.MethodsWe retrospectively reviewed 259 patients with hypermetabolic LNs who underwent pretreatment 18F-FDG PET/CT and were pathologically confirmed as NSCLC from two centers. Two hundr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 36 publications
0
9
0
1
Order By: Relevance
“…Herein we demonstrated that the combination of radiomic features of primary tumor and lymph node based on PET/CT improved the LNM diagnostic sensitivity, specificity and accuracy from 0.59, 0.38, and 0.50 of the TPC model and 0.92, 0.41, and 0.70 of the LPC model to 0.93, 0.75, 0.85 of the TLPC model in the testing set. The combination yielded better diagnostic efficacy than most of the existing forecasts, with values much higher than those of previous studies (for which sensitivity, specificity, and accuracy in the testing set ranged from 0.64, 0.94, 0.77 to 0.82, 0.89, 0.85, respectively) (Wang et al 2017 ; Cong et al 2020a , 2020b ; Ouyang et al 2021 ; Zheng et al 2021 ). These findings supported the necessity of comprehensive analysis of each lesion when evaluating the clinical stage of lung cancer patients; this approach may also be necessary for evaluating therapeutic efficacy or prognosis of lung cancer patients.…”
Section: Discussionmentioning
confidence: 55%
See 1 more Smart Citation
“…Herein we demonstrated that the combination of radiomic features of primary tumor and lymph node based on PET/CT improved the LNM diagnostic sensitivity, specificity and accuracy from 0.59, 0.38, and 0.50 of the TPC model and 0.92, 0.41, and 0.70 of the LPC model to 0.93, 0.75, 0.85 of the TLPC model in the testing set. The combination yielded better diagnostic efficacy than most of the existing forecasts, with values much higher than those of previous studies (for which sensitivity, specificity, and accuracy in the testing set ranged from 0.64, 0.94, 0.77 to 0.82, 0.89, 0.85, respectively) (Wang et al 2017 ; Cong et al 2020a , 2020b ; Ouyang et al 2021 ; Zheng et al 2021 ). These findings supported the necessity of comprehensive analysis of each lesion when evaluating the clinical stage of lung cancer patients; this approach may also be necessary for evaluating therapeutic efficacy or prognosis of lung cancer patients.…”
Section: Discussionmentioning
confidence: 55%
“…High-throughput radiomics has recently emerged as a powerful approach for identification of imaging biomarkers that can be used to build decision-support systems for cancer treatment (Hyun et al 2019 ) ( Lee et al 2015 ). Machine learning can be significantly effective for object detection and classification, and it is being increasingly used to help clinicians predict LNM based on radiomic features of primary tumors or lymph nodes (Goldstraw et al 2016 ; Cong et al 2020a ; Ouyang et al 2021 ; Zheng et al 2021 ; Scrivener et al 2016 ; Li et al 2015 ) with area under the curve (AUC) ranging from 0.77 to 0.86 . However, few studies have combined radiomic features of primary tumor and lymph node extracted from PET/CT images to build a LNM prediction model by applying radiomics and machine learning (ML).…”
Section: Introductionmentioning
confidence: 99%
“…PET radiomics in pulmonary oncology gathered 107 articles [ 83 , 84 , 85 , 86 , 87 , 88 , 89 , 90 , 91 , 92 , 93 , 94 , 95 , 96 , 97 , 98 , 99 , 100 , 101 , 102 , 103 , 104 , 105 , 106 , 107 , 108 , 109 , 110 , 111 , 112 , 113 , 114 , 115 , 116 , 117 , 118 , 119 , 120 , 121 , 122 , 123 , 124 , 125 , 126 , 127 , 128 , 129 , 130 , 131 , 132 , 133 ,…”
Section: Resultsunclassified
“…Similar studies have tried to predict the nodal status of lung cancer and other disease entities [23][24][25]. The authors of [23] applied a LASSO [26] model to directly estimate the N-stage on a per-patient basis using clinical information and features derived from PET/CT. They evaluated the model discrimination, not the calibration, in a single train/test split and a small external validation cohort.…”
Section: Discussionmentioning
confidence: 99%
“…Predicted outcomes were composed of the severity of pulmonary lesions, epidermal growth factor receptor status, or survival outcomes [28][29][30][31][32][33]. In contrast, we focus on the per-node dignity of thoracic lymph nodes, where rather little research has been conducted [23,24]. However, the potential synergies of applying radiomics and machine learning to the primary tumor and the thoracic lymph nodes remain subject to future research.…”
Section: Discussionmentioning
confidence: 99%